A review of climate change studies on paddy agriculture in Indonesia. Issue 1 (1st December 2022) - Ikhwali, M F; Nur, S; Darmansyah, D; Hamdan, A M; Ersa, N S; Aida, N; Yusra, A; Satria, A
Abstract: Indonesia is often referred to as an agricultural country as most of its population is working in agricultural sectors. Rice is one of the staple foods of the Indonesian people. The issues concerning the global climate change impose a potential threat on Indonesia's food security as the rice crop is extremely sensitive to climate change. The IPCC has released climate change scenarios as highlighted in Fifth Assessment Report (AR5) that could contribute positively to projecting the possible condition of future rice farming in Indonesia. Therefore, the goal of this research is to examine how far the Representative Concentration Pathway (RCP) scenarios have been implemented in relevant studies relating the rice farming. By 2021, the RCP scenarios in Indonesia at least have been studied and used in 13 relevant publications. The type of scenario used is mostly dominated by RCP8.5 scenario which is accounted used by 11 publications. Basically, the RCP8.5 is a scenario that projects the climate change with minimal efforts in reducing the emissions and expose the failures to tackle the global warming by 2100. Based on the findings of those research, it is possible to assume that the rice farming in Indonesia is going to face enormous challenges, particularly the potential decline in rice productivity. The emergence of those studies that interrelate the rice farming and climate change definitely will provide the initial footsteps to figure out on how to deal with future weather conditions.